Kodok: Komparatif Teks Naratif Bali dengan Cerita Rakyat Jepang - Wardana, I Wayan Kasu; Amanda Gayatri, Putu; Sri Pratekawati, Putu (Humanis; Vol 27 No 1 (2023), 2023)
This research is entitled “Frogs: The Comparison of Balinese Narrative Text with Japanese Folklore. The purpose of this research is to compare Geguritan Enggung with a Japanese folklore entitled "Kaeru Ny?b?". Kaeru Nyobo tells a story of Frog who plays a female character with a romance theme. This research applied a qualitative descriptive method using literary ecological theory and comparative literary theory. The findings in this study are the similarities and differences between the Balinese narrative text entitled Geguritan Enggung and the Japanese folklore entitled Kaeru Ny?b?. In addition, this research also found the meaning of the story of each of these stories.